Preterm Birth and Birth Weight and the Risk of Type 1 Diabetes in Chinese Children - Huang, Ke; Si, Shuting; Chen, Ruimin; Wang, Chunlin; Chen, Shaoke; Liang, Yan; Yao, Hui; Zheng, Rongxiu; Liu, Fang; Cao, Binyan; Su, Zhe; Mireguli, Maimaiti; et al. (Frontiers in Endocrinology, 2021)
Aims：Findings from previous studies about the association of preterm birth as well as birth weight with the risk of T1DM were still inconsistent. We aimed to further clarify these associations based on Chinese children and explore the role of gender therein. Methods: A nationwide multicenter and population-based large cross-sectional study was conducted in China from 2016 to 2019. Children aged between 3 and 18 years old with complete information were included in this analysis. Multiple Poisson regression models were used for evaluating the associations of birth weight as well as preterm birth with T1DM in children. Results: Out of 181,786 children, 82 childhood T1DM cases were identified from questionnaire survey. Children with preterm birth (<37 weeks) had higher risk of type 1 diabetes (OR: 3.17, 95%CI: 1.76-5.71). Children born with high birth weight (≥4,000g) had no statistically significant risk of T1DM (OR:1.71, 95%CI: 0.90-3.22). However, children’s gender might modify the effect of high birth weight on T1DM (girls: OR: 3.15, 95%CI: 1.33-7.47; boys: OR: 0.99, 95%CI: 0.38-2.55, p for interaction=0.065). In addition, children with low birth weight were not associated with T1DM (OR: 0.70, 95%CI: 0.24-2.08). The findings from matched data had the similar trend. Conclusions: In China mainland, preterm birth increased the risk of childhood T1DM, but high birth weight only affected girls. Therefore, early prevention of T1DM may start with prenatal care to avoid adverse birth outcomes and more attention should be paid to children with preterm birth and girls with high birth weight after birth.